The body schema and the multisensory representation(s) of peripersonal space. - Holmes, N; Spence, C (2004)
In order to guide the movement of the body through space, the brain must constantly monitor the position and movement of the body in relation to nearby objects. The effective 'piloting' of the body to avoid or manipulate objects in pursuit of behavioural goals (Popper and Eccles, 1977, p. 129), requires an integrated neural representation of the body (the 'body schema') and of the space around the body ('peripersonal space'). In the review that follows, we describe and evaluate recent results from neurophysiology, neuropsychology, and psychophysics in both human and non-human primates that support the existence of an integrated representation of visual, somatosensory, and auditory peripersonal space. Such a representation involves primarily visual, somatosensory, and proprioceptive modalities, operates in body part-centred reference frames, and demonstrates significant plasticity. Recent research shows that the use of tools, the viewing of one's body or body parts in mirrors, and in video-monitors, may also modulate the visuotactile representation of peripersonal space.